Yellow Perils of Robert Heinlein - John Hickman (European Journal of American Studies)
Yellow Peril and other anti-East Asian themes are a recurring but rarely acknowledged feature of the oeuvre of Robert A. Heinlein. Still revered by an overwhelmingly white, male and ideologically libertarian readership, the “Dean” of American Science Fiction made extensive use of threatening, hateful or contemptible images of East Asians in novels that appeared from the 1930s through the 1960s. The contradiction between Heinlein’s self-portrayal as broad minded and unbiased on issues of race and religion and the descriptions of East Asians as menacing and untrustworthy Others that suffuse his fiction has not been systematically investigated until now. Exposing Heinlein matters because he continues to enjoy a large readership and inspires other science fiction authors. The stereotyping expressed in novels like The Moon is a Harsh Mistress and the dehumanization expressed in novels like Starship Troopers continue to shape the social and political attitudes of non-East Asian Americans both in domestic race and ethnic relations and in international affairs.